SELF-CONCEPT OF TEENAGERS LIVING WITH PARENTS SINGLE PARENT IN SMPN 25 PADANG - Firsty Aufirandra; Khairani Khairani (Universitas Negeri Padang, 2021)
This research is motivated by the phenomenon of students of SMP N 25 Padang where students are faced with a single parent family condition which results in students not accepting the situation that occurs to their families and having jealousy towards friends who have complete families. This study aims to describe the self-concept of adolescents living with single parents at SMP N 25 Padang. The research method used in this research is quantitative method with descriptive type. The population in this study were all students at SMP N 25 Padang registered in 2019/2020 which were determined by 742 children, with a sample size of 50 students who obtained certain criteria purposively. The results showed that: (1) the self-concept of adolescents living with single parents at SMP N 25 Padang as a whole is in the low category with a percentage of 38%, (2) the self-concept of adolescents living with single parents at SMP N 25 Padang seen In terms of social aspects, it is in the very low category with a presentation of 52%, (3) the self-concept of adolescents living with single parents at SMP N 25 Padang, seen from the emotional aspect, is in the low category with a presentation of 42%, (4) teenage self-concept Those who live with single parents at SMP N 25 Padang from a moral perspective are in the low category with a percentage of 52%, (5) the self-concept of adolescents who live with single parents at SMP N 25 Padang seen from a cognitive perspective is in the low category with a percentage of 40 %.